IMPROVING LEARNING OUTCOMES AND INTEREST IN LEARNING HISTORY BY USING ROLE PLAYING METHOD FOR CLASS XI IPA 4 STUDENTS IN SMA NEGERI 10 PEKANBARU - Nurani, Zun (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is a classroom action research. The research process consisted of four stages, namely planning, implementation, observation, and evaluation. The study consisted of two cycles. The research subjects were class XI IPS 4 SMA Negeri 10 with 35 students who had taken the historical subject of the development of Indonesian society since the proclamation and guided democracy. In the pre-cycle, the student learning outcomes were average of 75.49 with 12 students passed, and 23 students didn't pass. In the first cycle, 22 students (62.68%) passed while 13 students (37.14%) failed. Cycle II all passed with an average value of 85.91, which was previously 79.94 in cycle I. For the pre-cycle, the highest score was 85 and the lowest was 64. In the cycle I, the highest score was 90 and the lowest was 70. For cycle II, the highest was 95 and the lowest was 80. From the learning process series, students’ learning outcomes had reached the KKM set by the school, which is 79. For the assessment of learning interest, point one with 10 people (28.57%) were neither agree nor disagree, point two with 10 people (28.57%) were strongly agree, point three with 13 (37.14%) were strongly agree, point four with 15 people (42.84%) were strongly agree, and point five with 11 people (31.41%) were agree. Therefore, the average score of students' interest tended to strongly agree.